Loss, survive, thrive : bereaved parents share their stories of healing and hope - Beck, Meryl Hershey (Rowman & Littlefield, 2019)
It feels completely unnatural for children to predecease their parents. According to one study, 19% of parents outlive their children-- often carrying the weight of horrendous grief to their own graves. Each chapter in this collection is an inspirational story written with a parent who also experienced the agony of losing a child, reclaimed his/her vitality, and is now living a fulfilling life. This book is a giant step toward healing the grieving heart.